2019
DOI: 10.1038/s41398-019-0679-z
|View full text |Cite
|
Sign up to set email alerts
|

Structural brain abnormalities in children and adolescents with comorbid autism spectrum disorder and attention-deficit/hyperactivity disorder

Abstract: Autism spectrum disorder (ASD) and attention-deficit/hyperactivity disorder (ADHD) share high rates of comorbidity, with the Diagnostic and Statistical Manual of Mental Disorders-Fifth Edition now acknowledging the comorbid diagnosis of ASD and ADHD. Although structural abnormalities in the prefrontal cortex, cerebellum, and basal ganglia occur in both ASD and ADHD, no structural studies have focused exclusively on patients with comorbid ASD and ADHD. We thus aimed to clarify the structural features and develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 47 publications
4
28
0
Order By: Relevance
“…Concerning the postcentral gyrus, volume abnormalities reported in this brain region in ASD have been inconsistent [31]. Mizuno et al [31] reported decreased left postcentral gyrus volume in ASD , while Brieber et al [32] described increased volume in this brain region in patients with ASD comparing with TDs. This may be due to the small sample sizes, the different proportions of females with ASD, and the different image processing techniques among different studies.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the postcentral gyrus, volume abnormalities reported in this brain region in ASD have been inconsistent [31]. Mizuno et al [31] reported decreased left postcentral gyrus volume in ASD , while Brieber et al [32] described increased volume in this brain region in patients with ASD comparing with TDs. This may be due to the small sample sizes, the different proportions of females with ASD, and the different image processing techniques among different studies.…”
Section: Discussionmentioning
confidence: 99%
“…This was observed through magnetic resonance imaging in both children and preadolescents, but was absent in adolescents. The authors suggested that pathophysiology in these comorbid patients may be related to somatosensory deficits and delayed maturation in this area [ 105 ].…”
Section: Changes In Brain Structure and Function In Adhd Patientsmentioning
confidence: 99%
“…Abnormalities in the basal ganglia were found in some psychiatric disorders (e.g., attention deficit hyperactivity disorder; ADHD). The prefrontal cortex and the basal ganglia (particularly the caudate nucleus) exhibit increased volumes [ 51 , 52 , 53 , 54 ].…”
Section: Differential Diagnosismentioning
confidence: 99%